Exploring Moral Values in the Indonesian EFL Textbook ‘English for Nusantara’: A Critical Discourse Analysis - Supriatna, Deri; Fikri, Fakhri; Irawan, Bambang; Sulaeman, Dedi (Academia Publication, 2025)
This study explores the representation and integration of moral values in English for Nusantara, an official English as a Foreign Language (EFL) textbook used in Indonesian secondary schools. Utilizing a qualitative research design grounded in Fairclough’s three-dimensional model of Critical Discourse Analysis (CDA), this research analyzes how moral values are constructed through textual features, discursive practices, and sociocultural contexts. Data were collected by systematically examining reading texts, dialogues, exercises, and visual materials across all units of the textbook. The analysis followed three stages: textual analysis, interpretation of discursive practices, and explanation of sociocultural implications. The findings reveal two dominant patterns: (1) the implicit and explicit embedding of moral values through character-driven scenarios and cultural narratives, and (2) the integration of local wisdom and universal values fostering multicultural awareness. These findings underscore the textbook's dual function as both a language learning tool and a medium for moral education, in line with Indonesia’s character education policy. The study offers implications for curriculum developers, textbook authors, and language educators in designing culturally grounded and value-oriented EFL materials.